Σαλμεσχ(ο)ινιακά: Measurement Standards of Astrotheology?: A New Approach to the Meaning and the Relevance of the Term - Akridas, Anastasios-Grammenos ca. 20./21. Jh. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
The meaning and the reference of the obscure term Σαλμεσχ(ο)ινιακά has been on debate more than a century among the scholars. In this article we try to unroll the thread of the research regarding the term, to detect and explain the context in which is referred, to solve the mystery of its etymology and to propose a brand new semantic core, which characterizes a whole stream of esoteric traditions, indicating the anthropomorphical representation of the deity, by giving the ecstatic description of its astral body and the measurement of its enormous and cosmic dimensions.